Striving to provide conditional access: strategies parents use to mediate the screentime of their children with autism spectrum disorder - Ebrahim, Faatima; Gretschel, Pamela; Abbas, Iesrafeel (Frontiers in Child and Adolescent Psychiatry, 2025)
IntroductionThere has been a growing presence of screentime, in the lives of children, with an escalation in use during the COVID-19 pandemic restrictions. Children with autism spectrum disorder show a particular preference for engagement in screentime. Gaining parental understandings of the steps they take to mediate excessive screentime can assist in developing interventions which mitigate the well documented negative impacts of screentime for children with autism spectrum disorder. This paper presents the findings of a study which explored parental perceptions of the screentime use and the strategies parents used to manage the screentime engagement of their children with autism spectrum disorder.MethodsA qualitative descriptive design, using semi-structured, in-depth interviews with seven purposively selected parents, was used to achieve the above objectives. Data was thematically analysed using an inductive approach.ResultsOne of the four themes generated during the study; Striving to provide conditional access to screentime details the varied mediation strategies parents used to manage their child's screentime under the two categories of Content monitoring and Setting limits.DiscussionThe findings of this study, describing the various restrictive strategies parents use to manage the screentime use of their children, were comparable to prior studies. Findings that built on existing evidence, describe the strategies parents used i.e., distraction and preparing for the cessation of screentime, to manage screentime in a way that avoided negative behaviour in their child and parental stress linked to this behaviour. It is certain, that screentime will remain a predominant occupation for children with autism spectrum disorder therefore, early childhood interventionists need to consider how to optimize the nature of engagement of screentime.